Scholarly Output on Dentistry and COVID-19: A Global Bibliometric Analysis - Sushmitha Mohana Murali; Karpagam Senthamarai Kannan; Merrylda Claribel S; Mohammed Haroon A L; Vettrichelvan Venkatasamy; Keerthiga Govindarajan; Sendhilkumar Muthappan (Medsci Publications, 2023)
Background: Bibliometric studies help in quantifying the pattern of research published in a particular area of interest to get the measure of research productivity. In this context, we analyzed the dental and COVID-19 research papers published from December 2019 to January 2021 globally. Method: The articles were retrieved from the PubMed and WHO COVID -19 databases using MeSH terms and keywords. The data downloaded as excel and extracted bibliometric information's and analyzed using Epi-info (7.2) software. Result: We obtained 800 research articles after removing duplicates and non-relevant articles from 1,823 articles from these two databases. The articles were published by 475 institutions in 62 countries. Among the listed countries, more publications were done by the United States of America (USA) (n=135;16.8%). The majority of the papers were published in June 2020 (n=114). The King's College London had the most number of publications (n=15; 1.9%). The majority of the articles were original articles (n=592; 74%). Conclusion: The study reports a gradual increase in publications over the months and a slowing down at the end of the year. The countries such as the USA, England, Italy, and China published more articles and this correlates with the number of covid-19 cases.